Valorization of agro-industrial wastes to produce volatile fatty acids: combined effect of substrate/inoculum ratio and initial alkalinity. Issue 25 (10th November 2021) - Iglesias-Iglesias, Ruth; Fernandez-Feal, María Mercedes del Coro; Kennes, Christian; Veiga, María C.
ABSTRACT : Agroindustry generates huge amounts of wastes leading to environmental problems in the zones where they are disposed. One of the strategies for the valorization of these wastes is the acidogenic fermentation used to produce volatile fatty acids. In this study, four agroindustrial wastes generated in different Spanish industries were selected for evaluating their acidogenic potential in batch assays. The selected wastes were potato solid waste, grape marc distilled, grape marc and brewery spent grain. Potato solid waste and grape marc presented the highest degree of acidification (69% and 54%, respectively) with the predominance of acetic, butyric and propionic acids in their VFA profiles. In the potato solid waste, the influence of two parameters, substrate/inoculum ratio and initial alkalinity added, on the degree of acidification and on the VFA profile was evaluated. The maximum VFA production (higher than 70% of the total COD added) was obtained at substrate/inoculum ratios of 1.5 and 2.8 g VS substrate g −1 VS inoculum and at the highest concentration of initial alkalinity (3 g L −1 as CaCO3 ). Additionally, it was demonstrated that an increase of initial alkalinity, at all S/I ratios, can shift the VFA profile obtained, decreasing the relative amount of butyric and propionic acids and increasing the amount of acetic acid. GRAPHICAL ABSTRACT: UF0001